1998
DOI: 10.1103/physrevb.58.8428
|View full text |Cite
|
Sign up to set email alerts
|

Detection of photoinduced electronic, thermal, and acoustic dynamics of gold film using a transient reflecting grating method under three types of surface plasmon resonance conditions

Abstract: Mechanisms of unusual signal enhancement observed for transient reflecting grating ͑TRG͒ experiments are investigated under three types of surface plasmon resonance ͑SPR͒ conditions, where two pump beams only, a probe beam only, or two pump beams and a probe beam, excite surface plasmon. A gold thin film deposited on a glass prism is measured in the Kretschmann configuration with a temporal resolution of tens of picoseconds. The signal under each SPR condition exhibits different characteristic features in sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In recent works by Katayama et al (84,85), the opposite findings were reported under surface plasmon resonance (SPR) conditions, which can provide a method to observe responses of the electronic grating, temperature grating, and acoustic grating separately. A surface plasmon (SP) is a kind of surface-localized plasma wave propagating parallel to a metal-dielectric interface, which can be optically excited in an attenuated total-reflection configuration.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…In recent works by Katayama et al (84,85), the opposite findings were reported under surface plasmon resonance (SPR) conditions, which can provide a method to observe responses of the electronic grating, temperature grating, and acoustic grating separately. A surface plasmon (SP) is a kind of surface-localized plasma wave propagating parallel to a metal-dielectric interface, which can be optically excited in an attenuated total-reflection configuration.…”
mentioning
confidence: 80%
“…Heterodyne detection combined with diffraction optics improves sensitivity significantly (80,82). Use of plasmon resonance makes it possible to separately detect electronic, thermal, and acoustic contributions at the same time that signal enhancement is achieved (84,85). These techniques are just beginning to be applied, but they should be major tools for femtosecond-TG experiments, material evaluations, and interface studies.…”
Section: Experimental Arrangementmentioning
confidence: 96%
See 1 more Smart Citation
“…Rapid thermal expansion launches a standing SAW with a well-defined wavelength and propagation direction determined by the spacing and orientation of the grating, respectively [31,2]. A displacement of less than a nanometer gives a strong diffraction signal on the order of 10 À4 of the incident probe intensity [3].…”
Section: Article In Pressmentioning
confidence: 99%
“…As a photothermal method, we have developed a transient reflecting grating (TRG) method with a time resolution of 80 ps, and have applied it to semiconductor surfaces. 8,9 The TRG method has many advantages, such as surface selectivity, high sensitivity, background-free detection, and providing directional information. We can expect to observe carrier thermalization and carrier transport dynamics by raising the time resolution to the femtosecond time region of the TRG method.…”
mentioning
confidence: 99%